2020
DOI: 10.1111/ppl.13272
|View full text |Cite
|
Sign up to set email alerts
|

Coping with inclement weather conditions due to high temperature and water deficit in rice: An insight from genetic and biochemical perspectives

Abstract: Climatic fluctuations, temperature extremes, and water scarcity are becoming increasingly unpredictable with the passage of time. Such environmental atrocities have been the scourge of agriculture over the ages, bringing with them poor harvests and threat of famine. Rice production, owing to its high-water requirement for cultivation, is highly vulnerable to the threat of changing climate, particularly prolonged drought and high temperature, individually or in combination. Amidst all the abiotic stresses, heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 141 publications
(261 reference statements)
0
4
0
Order By: Relevance
“…At present, a large number of heat resistance related genes have been identified, which has provided some help for heat resistance breeding of rice. However, the number of successfully cloned genes is very limited (Table 1) (Rabara et al, 2021). Therefore, it is still the focus of rice heat tolerance research to successfully clone the identified heat tolerance genes and make them be used in breeding practice.…”
Section: Breeding Heat Tolerant Rice By Genetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a large number of heat resistance related genes have been identified, which has provided some help for heat resistance breeding of rice. However, the number of successfully cloned genes is very limited (Table 1) (Rabara et al, 2021). Therefore, it is still the focus of rice heat tolerance research to successfully clone the identified heat tolerance genes and make them be used in breeding practice.…”
Section: Breeding Heat Tolerant Rice By Genetic Methodsmentioning
confidence: 99%
“…This undoubtedly provides a new channel for breeding rice with heat tolerance. However, although many heat tolerance related regulatory loci and QTLs have been reported, these studies cannot further improve rice yield (Khan et al, 2019;Rabara et al, 2021). In other words, these studies can only guarantee the stability of rice yield under various high temperature conditions.…”
Section: Breeding Heat Tolerant Rice By Genetic Methodsmentioning
confidence: 99%
“…Inconsistent starch content is thought to be affected by differences in glutinous rice varieties' response, which is assumed by differences in gene expression. Based on the research results by Rabara et al (2021), each variety has different genetic, morphological, and physiological characteristics. Different types of rice can affect diversity; thus, it affects starch metabolism and accumulation.…”
Section: Starch Content and Amylosementioning
confidence: 99%
“…The phenomenon affects the regularity and number of hydrological fluctuations, particularly in developing nations. Drought stress has been identified as a major threat to rice production [3].…”
Section: Introductionmentioning
confidence: 99%